Primary Epithelioid Sarcoma of Frontotemporal Scalp: a Rare Case Report with Recent Literature Review - Adhikari, Ganga D; Mandal, Sandip Kumar; Gnawali, Suman; Shrestha, Gyan B; Sharma, Nitu; Yadav, Ajay Kumar (Nepalese Journal of Cancer, 2023)
Epithelioid sarcoma (ES) is a very rare and aggressive mesenchymal sarcoma subtype which represents less than 1% of soft tissue sarcomas (STS). According to the origin of the site, there are two types of ES: distal-type epithelioid sarcoma and proximal-type epithelioid sarcoma. The clinical diagnosis of ES mainly is confirmed by histopathology examination followed by immunohistochemistry. Radical excisional surgery is the best treatment option for epithelioid sarcoma. According to TNM staging, the treatment option will vary from surgery to surgery accompanied with radiotherapy and chemotherapy. Here in, we presented a 36-year-old man had non-healing ulcer in left frontotemporal scalp extending to involve left orbit. Histopathological confirmed epithelioid sarcoma. Magnetic Resonance Imaging (MRI) of Head and Neck revealed that there was mass in left frontotemporal scalp measuring 6.7 X 5.7 X 2.6 cm extending to zygomatic region and left orbit D/D malignant mass/sarcoma with bilateral (B/L) sinusitis. After that patient undergone for Wide Local excision (WLE) surgery on 11th September 2022. Adjuvant Radiation Therapy (RT) 6000 cGy radiation dose in 30 fractions (#) which was 200 cGy per fraction (#) were given during 22nd September to 10th November 2022 due to local advancement of disease. Patient was asked to follow up after 6 weeks after completion of RT. After 6 weeks of surgery, the patient was undergone for MRI and report revealed normal study.